Ethnomathematics Peanut Cake in Learning Social Arithmetic - Nabila Adelia Dahlan; Siti Maysarah (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study examines ethnomathematical practices in a home-based peanut-cake (kue kacang) business and draws implications for teaching social arithmetic. Using a descriptive-qualitative, ethnographic approach, data were collected through observation, interviews, and documentation with the business owner, Mrs. Mardiana Rangkuti (Medan, Indonesia). Analysis reveals that key social-arithmetic concepts are embedded across procurement, processing, packaging, and sales, including gross, tare, and net calculations, unit conversions, pricing, profit, and profit percentage, with minimal risk of loss. Daily records indicate a profit rate of 233.52% relative to production costs, illustrating how routine commercial decisions operationalize mathematical reasoning. The study translates these authentic practices into context-rich classroom tasks (e.g., computing net weight from gross and tare, comparing pricing strategies, and evaluating profit percentages under varying input costs). The novelty lies in integrating local cultural and economic activities into mathematics instruction, enabling students to connect formal social arithmetic concepts with real-life contexts. This approach is expected to improve conceptual understanding, relevance, and engagement in learning social arithmetic.